Development Of Quality Management Islamic Education In Islamic Boarding School - Afiful Ikhwan (Al-Hayat: Journal of Islamic Education, 2017)
Islamic Boarding School is an educational institution that is irreplaceable by any educational institution, and it is still maintained. We know that the education of Islamic Boarding School in Indonesia at that time has not been standardized in a curriculum and is not organized as a systemic Islamic Boarding School Indonesia network. This means that every Islamic Boarding School has its own independence to apply curriculum and subjects that are in accordance with the flow of Islam that they follow, so that there is a boarding school that implements the curriculum of the Ministry of National Education by applying religious curriculum, then there is Islamic Boarding School who only wants to focus on the curriculum of knowledge Islam only, which means that the level of diversity of Islamic Boarding School models in Indonesia is not limited.